Who and how many can work from home in Norway? Evidence from task descriptions - Henning Holgersen; Zhiyang Jia; Simen Svenkerud (Statistics Norway, Research Department, 2020)
The COVID-19 crisis has forced great societal changes, including forcing many to work remotely (work from home) in an effort to increase social distancing. The ability to work fromhome has long been considered a perk, but we have few estimates of how many are actually able to work from home. This paper attempts to estimate the share of the Norwegian jobs that can be performed remotely by combining register-based labor statistics and the official documentationof the ISCO-08 standard. We find that approximately 39% of Norwegian jobs can be performedat home. The results suggest that the pandemic and the government's attempts to mitigate thiscrisis may have a quite uneven impact on the population. Those who are already disadvantagedare often less likely to have remote-friendly jobs and thus are hit more severely.
Keywords: D24; J22; J61; O30; R12; R32; 330; Covid-19; Working from home; Job advertisements; Unconventional data; Norway